Processing Attributes and Chips Quality of Promising Potato Clones under Different Slice Treatments in Bhaktapur, Nepal - Gainju, A.; Shrestha, A. K.; Manandhar, S.; Upadhyay, K. P.; Bhattarai, P. (Journal of the Institute of Agriculture and Animal Science, 2020)
A study was conducted to evaluate processing attributes of different potato clones (genotype) and their effect in chips quality in combination with different potato slice treatments in Bhaktapur, Nepal from January to April 2018. Six potato clones (PRP 35861.18, CIP 384866.5, PRP226267.11, CIP 388676.1, PRP 858676.1 and Desiree) were allocated in Randomized Complete Block Design with four replications. Significant variation among the potato clones was found with respect to dry matter and reducing sugar content. PRP 858676.1 showed the highest dry matter whereas the lowest reducing sugar content was with CIP 384866.5. Variation in specific gravity and total soluble solidwas not found statistically significant. Chips were prepared in two factorial design with 3 replications, following the protocol of National Potato Research Program. First factor was potato clones and the second factor was slice treatments viz; cold water, 0.5% NaCl solution and warm water at 45ºC. This study revealed significant variation in chips colour, taste & flavour, crispiness, overall acceptability and recovery percent. Clone CIP 388676.1 with slices treated with cold water produced best quality chips while highest recovery percent was given by PRP 858676.1 treated with warm water at 45ºC. Superior quality of chips was obtained with CIP 388676.1 followed by Desiree, CIP 384866.5 and PRP 858676.1. Thus, potato clones CIP 388676.1, Desiree, CIP 384866.5 and PRP 858676.1 needs further evaluation for chips quality and slice treatment with cold water should be recommended for good quality chips production.